The Effect of Economic Factors on Property Crime Rates (Universitas Negeri Semarang, 2022)
This research is motivated because the number of property crimes on the island of Sumatera is the highest in Indonesia during the 2014-2019 period. This study aims to examine the economic factors that influence property crime on the island of Sumatera. The type of data used is secondary data. The type of data used is panel data which is a combination of cross-section data from 10 provinces on the island of Sumatera and time series data for 2014-2019. The analytical method used is panel data regression analysis. The best model chosen is the Fixed Effect Model (FEM). The results of this study indicate that GRDP growth and unemployment have no significant effect, while poverty, income inequality, and per capita expenditure have a significant positive effect on property crime. The value of R2 is 0.9521, meaning that the independent variable can explain the dependent variable by 95.21%. Penelitian ini dilatarbelakangi karena jumlah kejahatan harta benda di Pulau Sumatera terbanyak di Indonesia selama periode 2014-2019. Penelitian ini bertujuan untuk meneliti faktor-faktor ekonomi yang mempengaruhi kejahatan harta benda di Pulau Sumatera. Jenis data yang digunakan adalah data sekunder. Tipe data yang digunakan adalah data panel yang merupakan kombinasi data cross section 10 Provinsi di Pulau Sumatera dan data time series tahun 2014-2019. Metode analisis yang digunakan adalah analisis regresi data panel. Model terbaik yang terpilih adalah Fixed Effect Model (FEM). Hasil penelitian ini menunjukkan bahwa Pertumbuhan PDRB dan pengangguran tidak berpengaruh signifikan, sedangkan kemiskinan, ketimpangan pendapatan dan pengeluaran per kapita berpengaruh positif signifikan terhadap kejahatan harta benda. Nilai R2 sebesar 0,9521, artinya variabel independen dapat menjelaskan variabel dependen sebesar 95,21%.